Pengaruh Faktor Internal dan Eksternal Terhadap Perilaku Kewirauhsaan Pengusaha (Suatu Studi Kasus pada Industri Kecil Bambu di Desa Sumber Agung, Kecamatan Moyudan Kabupaten Sleman) - Vonny Fitriarahmi; Teguh Kismantoroadji; Indah Widowati (Jurnal Dinamika Sosial Ekonomi, 2004)
This research is purposed: (1) to ascertain the influence of innovation, courage of taking the risk, and competence to the internal factor; (2) to ascertain the influence of market, business networking, and finance source to the external factor, (3) to ascertain the influence of managerial competence, self confidence, task and result oriented to the entrepreneurial behaviours of entrepreneur; (4) to ascertain the influence of internal factor and external factor to the entrepreneurial behaviours of entrepreneur. This research was using survey method, taking the entrepreneur sample was using simple random sampling method which in 41 entrepreneur. Collecting data was carried out through questioner, observation, in-depth interview, and documentation. The results of this research indicates that (1) the internal factor are influenced by innovation, courage of taking the risk, and competence; (2) the external factor are influenced by market, business networking, and finance source; (3) the entrepreneurial behaviours of entrepreneur are influenced by managerial competence, self confidence, also task and results oriented; (4) internal factor and external factor are influence to the entrepreneurial behaviours of entrepreneur.Keywords: entrepreneurial behaviours, internal factor, external factor